Prototype of a digital game for training executive functions in students with cerebral palsy - Stabile, Caroline Junqueira de Padua [UNESP]; Seabra Junior, Manoel Osmar [UNESP]; Araujo, Gisele Silva [UNESP]; Uchelli, Janiele de Souza Santos [UNESP] (Organizacion Estados Iberoamericanos Educacion Ciencia & Cultura-oei, 2024)
The objective of this study was to develop and validate a prototype of a digital game, for use as an Assistive Technology resource, for training the executive functions of working memory and selective attention in students with cerebral palsy. To this end, the study was developed in three stages. The first stage consisted of analyzing a set of guidelines in the literature that included information on the development of digital games for students with cerebral palsy. In the second stage, the Digital Game prototype was developed on the free Engine GDevelop platform, available for building digital games. Finally, in the third stage, the prototype of the digital game was validated by experts in the area of Special Education and games. This involved the formation of a discussion group, made up of six evaluators with experience in interventions with students with cerebral palsy. The results showed, after reaching a group consensus, the evaluators recommended some modifications in the development of prototype. Thus, it could be concluded that the prototype of the digital game attends the proposed executive functions and can be considered as an Assistive Technology resource for training students with cerebral palsy up to level 3 of GMFCS and MACS.
Keywords: special education; cerebral palsy; educational games; executive function; assistive technology